The impact of user search behavior on web search satisfaction - Mat Yamin, Fadhilah; T., Ramayah (2010)
This study investigates the information searching behavior of final year undergraduate students using self administered questionnaire. The focus of the study is on user behavior on query formulation. In this study, a total 1072 queries are used for the analysis.O ut of these totals, 596 queries are classified as breadth search query and 476 are depth search query. All queries are captured through search log and marked to determine its category (either breadth or depth search query). The impact of user search behaviour on web search satisfaction is analyzed using regression analysis. The findings indicate that search behavior is positively and significantly influenced the search satisfaction.